Enhancing crop and water productivity of Bt cotton (Gossypium hirsutum) through drip irrigation and fertigation in semi-arid environments of south-western Punjab - KAUR, SIMRANJEET; MISHRA, SUDHIR KUMAR; SINGH, KULVIR; PAL, R K; GILL, K K; KINGRA, P K (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during 2019 and 2020 at Regional Research Station (Punjab Agricultural University, Ludhiana, Punjab), Faridkot, Punjab to evaluate the impact of different drip irrigation and fertigation regimes on Bt cotton (Gossypium hirsutum L.) (cv. RCH 773 BGII). The experiment was conducted in a randomized complete block design (RCBD) comprised of 3 drip irrigation levels (60%, 80%, and 100% of ETc); 2 fertigation doses (75% and 100% of recommended nitrogen dose), along with two extra control treatments (surface flood irrigation with 105 kg N/ha and subsurface flood irrigation with 112.5 kg N/ha). Results revealed that surface drip irrigation significantly reduced water usage by 13.9–32.3% as compared to conventional surface flood irrigation, while seed cotton yield increased by 18.2–25.2%. Notably, subsurface drip fertigation (SSDF) (100% recommended level of nitrogen applied at 80% ETc) exhibited the potential to conserve about 8.9–25.7% of total water applied, besides boosting crop yield by 37.2%. In conclusion, this study elucidated better crop and water productivity with subsurface drip followed by surface drip irrigation as compared to traditional surface flood irrigation and manual fertilizer application. Therefore, adoption of drip irrigation systems for water and nitrogen application needs to be advocated for sustainable cotton cultivation.